The language of literacy education - Collet, Vicki (Brill, 2021)
"This volume is a valuable reference for literacy scholars and educators. In this encyclopaedic reference of prominent literacy terms, you will find citations of theorists and research findings to validate the content and lead you into a deeper dive for those terms of particular interest. Whether read cover to cover to provide an overview of the field or used as a side-table reference, The Language of Literacy Education offers valid, current information about important topics in the field. The 297 indexed terms expand our 87 main entries to encompass relevant terms in literacy education. Contributors are: Johnny B. Allred, Leah R. Cheek, Vicki Stewart Collet, Rebecca Carpenter de Cortina, Judy L. Fields, Seth D. French, Savanna L. Gragg, Angelia C. Greiner, Megan Yates Grizzle, Kathryn Hackett-Hill, Holly Sheppard Riesco, Afton Schleiff and Wyann Stanton"-- Provided by publisher
Keywords: Literacy -- Terms and phrases.; Literacy -- Study and teaching.; Literacy; Literacy -- Study and teaching; Dictionaries